Adequacy of clinical trial evidence of metformin fixed-dose combinations for the treatment of type 2 diabetes mellitus in India. Issue 2 (6th March 2018) - Evans, Valerie; Roderick, Peter; Pollock, Allyson M
Abstract : There is growing national and international concern about the drug regulatory system in India. Parliamentary reports have highlighted the presence of high numbers of unapproved medicines and irrational combinations of both approved and unapproved drugs in the Indian market-place. Fixed-dose combinations (FDCs) are a peculiar feature of the Indian pharmaceutical landscape. Although metformin is a first-line treatment, FDCs for diabetes in India account for two-thirds of all diabetes medicine sales, and some have not been approved by the Central Drugs Standard Control Organization (CDSCO). This study examines the basis of efficacy and safety of top-selling metformin FDCs in India against four WHO criteria from clinical trials guidelines for the approval of FDCs. Data from a commercial drug sales database (PharmaTrac) were combined with searches through published literature, clinical trial registries, and published and unpublished trial websites of metformin FDCs in adults with type 2 diabetes mellitus. Five metformin FDCs in India from November 2011 to October 2012 accounted for 80% of all metformin FDC sales by value and volume. Although all five had obtained CDSCO approval, three had been sold and marketed prior to receiving this approval. Evaluation of published and unpublished clinical trials of these five FDCs found none provided robust evidence of safety and efficacy for the treatment of type 2 diabetes. Recommendations are made for publishing evidence that underpins drug approvals, marketing bans, greater transparency through updated clinical trials databases and legislative reform in order to prevent irrational FDCs from entering the market.